Online Identity Analysis of Public Figure Raffi Ahmad : Analisis Identitas Online Tokoh Publik Raffi Ahmad - Wardhana, Bagas Kusuma; Rohman, M. Alim Syafiur; Febriana, Poppy (Procedia of Social Sciences and Humanities, 2025)
Raffi Ahmad has successfully created a strong and contemporary online persona, leveraging comedy, character personification, and customizable content to stay relevant in the digital world. He has navigated the challenges of online reputation and audience engagement with ease. However, there is a need for further strategic measures to safeguard his privacy and protect against the risks associated with negative participatory surveillance. This analysis explores how Raffi Ahmad has built and maintained his digital identity, managed interactions with his diverse audience, and dealt with privacy and reputation concerns in the digital era. The findings suggest that while Raffi has established a powerful online presence, there are critical areas where more proactive measures are needed to protect his personal information and reputation. Highlights: Strategic Digital Identity – Raffi Ahmad effectively uses humor, character personification, and interactive content to maintain a strong and adaptable online persona. Audience Engagement & Reputation Management – He skillfully navigates audience interactions and online reputation, ensuring sustained relevance in the digital space. Privacy & Security Risks – Despite his success, proactive measures are needed to safeguard his personal information and mitigate risks from negative participatory surveillance. Keywords: Raffi Ahmad, Social Media, Public Figure